Legalitas Tindakan Pemerintah Daerah Dalam Pengalihan Fungsi Trotoar Kota Ambon - Samal, Radhi Rafiq Defrian; Irham, Muhammad; Matitaputty, Merlien Irene (Faculty of Law Universitas Pattimura, 2024)
ABSTRACT: Article 34 paragraph 3 of the Constitution of the Republic of Indonesia states that the state is responsible for providing health service facilities and adequate public service facilities to the community. Furthermore, Article 45 paragraph 1 letter a of Law Number 22 of 2009 concerning Road Traffic and Transportation